Tradeoffs and Depletion in Choice - WANG, Jing (Institutional Knowledge at Singapore Management University, 2010)
Four experiments examine why choices deplete executive resources. The authors show that the resolution of trade-offs is a driver of depletion effects arising from choice, and the larger the trade-offs, the greater is the depletion effect. The authors also find that choice difficulty not related to trade-offs does not influence the depleting effect of the choices. Finally, the authors find that though people can intuit some depletion effects, they do not intuit that choices or trade-offs within choices might be depleting and therefore fail to predict that larger trade-offs are more depleting.